2020
DOI: 10.1111/php.13340
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome A and its Functional Manifestations in Etiolated and Far‐red Light‐grown Seedlings of the Wild‐type Rice and its Hebiba and Cpm2 Mutants Deficient in the Defense‐related Phytohormone Jasmonic Acid

Abstract: Interaction between phytochromes and hormones is becoming one of the major issues in plant photophysiology. In this work, effects of defense‐related jasmonic acid (JA) on phytochrome A (phyA) were investigated by fluorescence spectroscopy making use of two JA biosynthesis mutants of rice: cpm2 with the inactivated gene allene oxide cyclase and hebiba with additional genes deleted. Constant far‐red light (FRc) mediated by phyA reduced its content in the wild type (WT) and mutants, and brought about domination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…They are controlled primarily by phyA because light, which travels from stems to roots through the vascular tissue, is highly enriched with the farred component sensed exclusively by phyA. Our experiments with rice seedlings grown in darkness and under constant and pulsed far-red light (light conditions favorable for the HIR and VLFR response types, respectively) have shown that the downregulation of roots' growth is observed only under constant FR [12]. Taking in consideration that phyA″ and phyA′ mediate HIR and VLFR, respectively [9], we may conclude that this root growth rate reduction is controlled by phyA″, whereas phyA′ is inactive.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…They are controlled primarily by phyA because light, which travels from stems to roots through the vascular tissue, is highly enriched with the farred component sensed exclusively by phyA. Our experiments with rice seedlings grown in darkness and under constant and pulsed far-red light (light conditions favorable for the HIR and VLFR response types, respectively) have shown that the downregulation of roots' growth is observed only under constant FR [12]. Taking in consideration that phyA″ and phyA′ mediate HIR and VLFR, respectively [9], we may conclude that this root growth rate reduction is controlled by phyA″, whereas phyA′ is inactive.…”
Section: Discussionmentioning
confidence: 76%
“…In the mutants, both constant FR and pulsed FR were active in rice roots' growth reduction, in contrast to the wild type where pulsed FR was inactive. This phyA activity in the mutants correlated with the higher phyA′ content and phyA′/ phyA″ proportion in them compared with the wild type [12]. This suggests that phyA′ is active in the mutants, but in the wild-type JA suppresses its activity.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In general, there is a very close connection between phyA functions and the hormonal status of the plant (see reviews [160][161][162][163][164][165][166]). We investigated the effects of the hormone jasmonic acid (JA) on the phyAs and their functions [167,168]. JA controls different aspects of plant growth and development, including inhibition of seed germination and root growth and stimulation of degradation of chloroplast proteins and leaf senescence (for review on JA see [160,[169][170][171]).…”
Section: The Phyas Mediate Distinct Types Of Photoresponses: the Majo...mentioning
confidence: 99%